2011
DOI: 10.1007/s12550-011-0096-5
|View full text |Cite
|
Sign up to set email alerts
|

Impact of aggressiveness of Fusarium graminearum and F. culmorum isolates on yield parameters and mycotoxin production in wheat

Abstract: Plant-associated isolates from Fusarium graminearum and F. culmorum were inoculated on wheat in field experiments in 2007 and 2008 to ascertain their influence on fungal colonization of the ears, as well as mycotoxin contamination (deoxynivalenol, DON; nivalenol, NIV; zearalenone, ZEA) and yield parameters in the mature crop after inoculation with or without irrigation. The isolates were assigned to four different groups of aggressiveness on the basis of pathogenic symptom development and mycotoxin production … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
16
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 17 publications
(16 citation statements)
references
References 38 publications
(48 reference statements)
0
16
0
Order By: Relevance
“…Fusarium culmorum and F. graminearum as well as A. tenuissima used in the present study were aggressive colonizers of wheat ears and well known producers of mycotoxins in grains (Korn et al . ). Under natural field conditions, the ripening grain ears are colonized by several saprophytic and pathogenic fungi (Dawood ; D'Mello et al .…”
Section: Discussionmentioning
confidence: 97%
See 3 more Smart Citations
“…Fusarium culmorum and F. graminearum as well as A. tenuissima used in the present study were aggressive colonizers of wheat ears and well known producers of mycotoxins in grains (Korn et al . ). Under natural field conditions, the ripening grain ears are colonized by several saprophytic and pathogenic fungi (Dawood ; D'Mello et al .…”
Section: Discussionmentioning
confidence: 97%
“…; Korn et al . ), probably based on enzyme activities, ascospore production and metabolite profiling. However, to our knowledge, similar enhancement of fungal growth in cocultures has never been described before in the literature.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In a field study by Schade-Schütze et al (2000), inoculation of wheat spikes with F. culmorum reduced 1000 kernel weight by 14-61 %. Korn et al (2011) demonstrated that the F. culmorum isolate was characterized by higher aggressiveness in wheat heads than F. graminearum isolates, and that its aggressiveness only partially resulted from the production of mycotoxins such as deoxynivalenol, nivalenol and zearalenone. In our study, higher grain filling rates were noted for winter wheat spikes non-inoculated with F. culmorum and protected with A. pullulans, compared with untreated spikes.…”
Section: Discussionmentioning
confidence: 99%